Management of Mango Powdery Mildew through Potential Organic Products - Kulkarni, Shripad; Chavan, Tippesh; Vijaykumar, K. N. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at farmer’s field in Kyarakoppa village of Dharwad taluka, Karnataka, India during 2014–15 and 2015–16. Mango (Mangifera indica L.) is considered as one of the most important fruit crop for millions of people in the world, particularly in India where it is deemed to be the choicest of all indigenous fruits. Mango powdery mildew caused by Oidium mangiferae Berthet is a severe disease that infects all parts of mango trees except the fruits. Organic production has recently increased the demand for environmental friendly control programs to eliminate the risk of fungicide and pesticide resistance so, it is important to study the alternatives from natural extractions. Hence, the present investigation was carried to evaluate the use of some eco-friendly compounds as alternatives to control the powdery mildew of mango. The results revealed that out of ten different treatments evaluated, the treatment T4 involving panchagavya @ 1:10 dilution has resulted in least mean disease severity of 30.27% and maximum net returns (` 1,12,900) as against 61.00% disease severity and minimum net returns (` 50,000) in the control. The treatment T4 was statistically on par with recommended fungicide sulphur @ 3 g l-1 which has resulted in 28.96% Disease Index over the years. However, the taste and smell were found to be superior with panchagavya sprayed trees which has produced yield 6.75 t ha-1 with cost benefit ratio of 5.11 as compared to C:B ratio of triadimefon (6.86) and sulphur (6.37).